A world history of Chinese literature - Zhang, Yingjin (Routledge, Taylor & Francis Group, 2024)
Modern Chinese literary historiography / David Wang -- Zeitgeist and literature : the reception of Chinese literature in Germany until the first half of the twentieth century / Weigui Fang -- Paris and the art of transposition, 1920s-1940s / Angie Chau -- Line, loop, constellation : classical Chinese poetry between Sinophone and Anglophone worlds / Luo Hui -- A decade apart : bridging the US and China literary systems, 2010-2021 / Jonathan Stalling -- Chinese literature at large : Wong Chin Foo's border-crossing writing / Ping Zhu -- Engaging the world in Republican literature / Liyan Qin -- The rise of author museums in the PRC : how institutions make world literature / Emily Graf -- Yi literature : traditional and contemporary / Mark Bender -- Queer Sinophone literature in Hong Kong : the politics of worldliness / Alvin K. Wong -- Taiwanese literature in the early twenty-first century / Kuei-fen Chiu -- Of other (Chinese) spaces : Sinophone literature and the rainforest / Andrea Bachner -- Modern Chinese drama across media and worlds : centered on the case of the White snake / Liang Luo -- Reportage and the forms of nonfiction art in China / Charles Laughlin -- Reading world literature in Chinese science fiction / Lena Henningsen -- Ecological critique as world literature : alienation of nature and humans in Chen Qiufan's Waste tide / Ban Wang -- Su Manshu's "Broken hairpin" : a romantic tragedy in the hard times / Ping-hui Liao -- Qian Zhongshu as a cosmopolitan / Ji Jin -- Zhang Ailing and the Cold War cultural geography / Xiaojue Wang -- Worlding Jin Yong's martial arts (wuxia) narrative in Three keys / Weijie Song -- Yan Lianke's heterotopic imaginaries / Carlos Rojas -- Modern intellectual masculinities in transformation / Jun Lei -- Nora in China / Ying Hu -- Reading women : rethinking a trope in the socialist modern and beyond / Barbara Mittler -- Feminine neorealist fiction in the new millennium : voice, trauma, and focalization in Fang Fang's fiction / Li Guo -- Frame tales : reading the 1,001 nights in early twentieth-century China / Michael Gibbs Hill -- Figuring time : lyricism in contemporary Chinese poetic films / Shengqing Wu -- Performance and performativity in modern China / Emily Wilcox -- Chinese internet fictions in the transmedia world / Yiwen Wang.
Keywords: Aufsatzsammlung; Geschichte 1900-2020; Literatur; Chinesisch